A Free Surface Flow under Gravity - Saadi, Manel; Bounab, Nadia: Supervisor (Mohamed Boudiaf University of M’sila, Faculty of Mathematics and Computer Sciences, Departement of Mathematics, 2024)
In this thesis , we have studied numerically a problem of two-dimensional potential flow in a channel with trapezoidal obstacle in the bottom , witch makes an angle = with the axis (xox ) taking into account the effect of gravity but surface tension efforts are neglected. We have used some conformal transformations and series truncation technique for obtain the numerical solution.
Keywords: Free surface; Potential flow; Schwartz –Christoffel; Transformation; Truncation of the series; Froude number